PERAN PARTAI EKS KOMBATAN TERHADAP ADVOKASI REPRESENTASI PEREMPUAN DALAM POLITIK PASCA KONFLIK: Studi Kasus Partai Aceh di Indonesia dengan Partai Farabundo Mart National Liberation Front (FMLN) di El Salvador, Amerika Latin - , REZKI SATRIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis deals with the role of the ex-combatant women advocacy against the devastating conflict by using a case study of Aceh and El Salvador. Aceh and El Salvador was chosen because it is two different areas but has similarities to the transformation of the movement of the armed struggle of the movement into a political party, movement through the general election The party was formed by ex-combatant under conflict after peace negotiations. Party ex-combatant who was later the subject of a case study in this research is the party of ex-combatant (Aceh party) in Aceh and the party Farabundo Mart National Liberation Front (FMLN) in El Salvador. The presence of excombatant party as part of the process of democratization had a different reception on the discourse of equality in participation and representation of women public spaces especially representation in politics. The Aceh party, the trend of women only as a formality to meet the quota of 30 per cent, without involving the woman seriously in political matters. This certainly can be seen how the program of the party that tends to gender bias. While in the FLMN women's political rights is the most basic human rights, while human rights are an integral part of democracy. El Salvador women not only considered as the fulfillment of a 30 percent quota, but also El Salvador women's unique role in the advocate for their rights, especially their representation in Parliament. The purpose of this research is looking at the phenomenon of the presence of the ex-combatant after the conflict as part of the process of democratization in providing advocacy on women. This study uses qualitative methods with secondary data is obtained through the study of librarianship by studying literature, scholarly writings, as well as documents relating to the object of research and the problems raised.